Is there a link between home ownership and unemployment levels? Evidence from German regional data - Oliver Lerbs (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
Using German regional data for 1998, 2002 and 2006, this study reexamines the Oswald hypothesis, the conjecture that high levels of home ownership lead to inferior outcomes in regional labor markets. Including a set of controls for regional unemployment rates, three different econometric models are specified and estimated: a cross-sectional model, a pooled data model, and a model taking into account unobserved time-invariant effects on regional unemployment rates. It is found that the link between home ownership and unemployment levels is inverse in cross-section but positive in panel estimations. The economic significance of the relationship is small in both cases, however. Factors like average labor productivity, participation, export orientation and human capital endowment clearly dominate the impact of home ownership on unemployment in German regions.
Keywords: J61; J64; R23; 330; Home ownership; unemployment; Oswald's hypothesis; German regions